Street Clinic Nursing for coping with vulnerabilities - Giulia Romano Bombonatti; Débora de Souza Santos; Dalvani Marques; Fernanda Mota Rocha (Universidade Federal do Ceará, 2021)
Objective: to unveil the perceptions of the Street Clinic nursing staff about coping with vulnerabilities. Methods: qualitative study, carried out by means of participant observation of the team's activities, recording in a field diary and semi-structured interviews with the nursing team, totaling 17 participants. Results: situations experienced by people living on the streets that deepen health inequities by violating rights were revealed. Among the nursing work tools, the potential of collaborative work, listening, and welcoming technologies stand out as mediators of a more humanized care. There is a need for specific strategies to guide nursing care on the streets. Conclusion: nursing has great potential for addressing the vulnerabilities of the homeless population using soft and soft-hard technologies.